Pengaruh komposisi MnFe2O4 terhadap sifat listrik nanokomposit MnFe2O4/ PVDF yang disintesis dengan metode spin coating (The effect of MnFe2O4 composition on the electrical properties of MnFe2O4 / PVDF nanocomposites synthesized by the spin coating method) - Onny Gustira; Yenni Darvina; - Ramli (PILLAR OF PHYSICS, 2020)
Manganese ferrite (MnFe2O4) has an MnFe2O4 structure in which its manufacture uses manganese mineral powder. MnFe2O4/ PVDF nanocomposites are made in the form of thin films to see the electrical properties that are affected by variations in composition. MnFe2O4/ PVDF nanocomposites were characterized using XRD, FTIR and FPP. The XRD characterization results show that the Monoclinic Crystalline form for PVDF and Cubic for MnFe2O4, the angular value of 2θ formed is the greater the composition of MnFe2O4 from small to large used, then MnFe2O4 and PVDF are already present in the MnFe2O4/ PVDF angles which are seen in the composition of MnFe2O4 from small to large used, then MnFe2O4 and PVDF are already present in MnFe2O4 / PVDF diffraction peak. FTIR characterization results can be seen that MnFe2O4 successfully binds to PVDF, where Fe-O is a functional group MnFe2O4 and CH2 is a PVDF functional group. The results of the FPP characterization show that if the MnFe2O4 composition is getting bigger and the PVDF composition is getting smaller, the resistivity value is small and the conductivity value is greater.